Raman spectroscopy in neurosurgery - Bergqvist, Saga (Luleå tekniska universitet, Institutionen för teknikvetenskap och matematik, 2020)
Brain tumors or brain cancer is a disease than affects people of all ages. The median age of a person living with a brain tumor is 60 years, it is however a disease that affects children and young adults in high grade. Brain cancer is the second most common type of cancer among children and is also the most common cause of cancer related death among this group. To ensure that the damages on the brain is as small as possible, it is important that a tumor can be diagnosed and removed as early as possible. Previous methods of diagnosis is based on biopsy where a part of the tumor is removed and examinated by a pathologist. This is a time consuming process that also is biased by the human factor, there is therefore a need for a method that can be used in situ with an unbiased result. One method that have shown great promise is photensitation with 5-Aminolevoluic acid (5-ALA). However, this method have shown to only work properly on tumors of high malignancy in adults. As a comlpiment to photosentisation, Raman spectroscopy have shown good promise in previous studies. This study was conducted to investigate the use of Raman spectroscopy as a tool for in situ brain tumor diagnostics. The use of Raman spectroscopy was tested by comparing two previously performed studies, where they looked at a number of Raman bands from biological markers that are known to change in cancerous tissue as well as the intensity ratio between some Raman bands. A measurement system for Raman spectroscopy was designed and built at Luleå University of Technology where the system were evaluated on tissue samples from conventional meat i.e. pork and beef to ensure that is was possible to achieve spectroscopic information of protein and lipid content in tissue. The measurement system was then transported to Linköpings University where the measurements on six brain tissue samples where performed. The samples came from five different tumors of which one tumor was thought to come from a high malignant tumor based on preliminary ...